A SURVEY ON USAGE ANALYTICS FOR IMAGING DIAGNOSTIC EQUIPMENTS - Verghese, Merin Susanna; R, Parvathi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
The main aim of the paper is to find the best predictive algorithm that can be used to predict the usage of the imaging diagnostic equipment in the near future. The growing number of patients are not able to receive the image diagnostic test within a short waiting time. The goal is to keep the waiting time low. The rising demand for the image diagnostics equipment has to be estimated to improve the service.